2022
DOI: 10.1007/s12264-022-00989-5
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical Circuit Controls Neuropathic Pain via Up-regulation of HCN2 in the Ventral Posterolateral Thalamus

Abstract: The thalamocortical (TC) circuit is closely associated with pain processing. The hyperpolarization-activated cyclic nucleotide-gated (HCN) 2 channel is predominantly expressed in the ventral posterolateral thalamus (VPL) that has been shown to mediate neuropathic pain. However, the role of VPL HCN2 in modulating TC circuit activity is largely unknown. Here, by using optogenetics, neuronal tracing, electrophysiological recordings, and virus knockdown strategies, we showed that the activation of VPL TC neurons p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…One week later, pain and anxiodepressive‐like behaviors were evaluated followed by the local infusion of either NS or ZD7288 (10 μg/kg, 200 nL on each side) into the LHb of SNI and Sham mice (Figure 8B ). 39 Results showed that compared with the NS‐infused group, the mechanical pain thresholds were significantly increased after the infusion of ZD7288 into the LHb at both 60 and 90 min in SNI 6w mice (Figure 8C ). Furthermore, the application of ZD7288 produced evident antidepressant effects in both FST and TST (Figure 8D,E ) and did not affect the motor activity of mice, as evaluated by the OFT (Figure 8F,G ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…One week later, pain and anxiodepressive‐like behaviors were evaluated followed by the local infusion of either NS or ZD7288 (10 μg/kg, 200 nL on each side) into the LHb of SNI and Sham mice (Figure 8B ). 39 Results showed that compared with the NS‐infused group, the mechanical pain thresholds were significantly increased after the infusion of ZD7288 into the LHb at both 60 and 90 min in SNI 6w mice (Figure 8C ). Furthermore, the application of ZD7288 produced evident antidepressant effects in both FST and TST (Figure 8D,E ) and did not affect the motor activity of mice, as evaluated by the OFT (Figure 8F,G ).…”
Section: Resultsmentioning
confidence: 93%
“…A double dummy cannula with a 0.5 mm extension beyond the tip of the guide cannula—secured with a dust cap—was inserted into the guide cannula to avoid clogging during the recovery period. 38 After a recovery period of at least 7 days, ZD7288 (10 μg/kg, Sigma) 31 , 39 dissolved in 0.9% saline (NS) was infused into each side of the LHb using a Hamilton micro‐syringe connected to a double injector cannula that was via a polyethylene pipe filled with mineral oil. A total volume of 200 nL of ZD7288 was infused at a rate of 100 nL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the lateral thalamus has been strongly implicated in chronic pain processing 126 , and exhibits plasticity following nerve injury 127 . Therefore, neuroplasticity in the VPL during pathological conditions [127][128][129] may alter how incoming tactile information is processed, which may aberrantly contribute to tactile-evoked pain perception. Further studies on how DCN input to the VPL is interpreted during naive and chronic pain conditions are required.…”
Section: Redundancymentioning
confidence: 99%
“…There are several parallels between injury-induced cellular changes in higher centres and those seen in the periphery or spinal cord. For example, peripheral neuropathy induces HCN channel dysfunction in medial prefrontal cortex ( 502 ) and thalamus ( 503 , 504 ) and Na v 1.3 function is altered in thalamic neurons ( 505 , 506 ). Both channel types are similarly affected by peripheral nerve injury ( 208 ).…”
Section: Role Of Supra-spinal Structures In Pain Etiologymentioning
confidence: 99%